Epidemiological profile of leprosy in Brazil (Research, Society and Development, 2024)
Leprosy is caused by the bacteria Mycobacterium leprae, it is an infectious disease with a prolonged latency period. Brazil is currently the second most endemic country in the world. It has great disabling potential, which is intrinsically related to stigma and prejudice about the disease. Currently, this disease persists as a public health problem in the world with strong social determination. Given this context, the objective of this study is to analyze the epidemiological profile of leprosy, at all ages, in Brazil and its regions, between 2012 and 2023. Methodology: This is an epidemiological study carried out based on data from the department of health information from the SUS (Unified Health System). The variables used were: hospital admissions, deaths, age group, color/race, sex, hospital expenses and health macro-region. Results: 49,229 hospitalizations occurred due to leprosy in the period analyzed. The biggest year for hospitalizations was 2013, the northeastern region is responsible for the highest number of hospitalizations and deaths. Interactions in the South region are more costly and the Southeast region is highlighted in the average period of leprosy patients. Men, mixed race, aged between 50 and 59 are the most affected. Conclusion: Knowing the pattern of leprosy in this population can support the planning of disease surveillance and control actions and attention to the proposed education actions must be redoubled.